2016
DOI: 10.1186/s12879-016-1490-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of reduced-dose intravitreal ganciclovir for cytomegalovirus retinitis

Abstract: BackgroundCytomegalovirus retinitis (CMVR) is one of the most common opportunistic infection in immunocompromised individuals. Intravitreal ganciclovir injection has been used successfully but no standard regimen was established. Risks of drug toxicity, endophthalmitis, and injection-related complications increased with number and frequency of injection. The aim of this study is to evaluate the outcomes of reduced-dose intravitreal ganciclovir (2 mg/0.04 mL) for the treatment of CMVR.MethodsA prospective obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The optimal regimen should balance between efficacy, treatment burden and potential retinal toxicity from prolonged and repeated injections [22][23][24] . The regimen used in this study has been demonstrated to be clinically effective and safe 25 . Nevertheless, no studies have evaluated the effects of intravitreal ganciclovir on microvascular retinal blood flow.…”
Section: Discussionmentioning
confidence: 93%
“…The optimal regimen should balance between efficacy, treatment burden and potential retinal toxicity from prolonged and repeated injections [22][23][24] . The regimen used in this study has been demonstrated to be clinically effective and safe 25 . Nevertheless, no studies have evaluated the effects of intravitreal ganciclovir on microvascular retinal blood flow.…”
Section: Discussionmentioning
confidence: 93%
“…The recommended dosage of intravitreal ganciclovir used to treat herpetic uveitis is 200–400 μg/0.1 ml. Intravitreal ganciclovir injection at doses of 1 mg, 2 mg, 3 mg and 5 mg has also been used to treat ARN and CMVR [ 2 , 6 8 ]. In one prospective interventional case series, intravitreal ganciclovir injection of 5 mg/0.1 ml once a week was used to treat active CMVR, and no retinal toxicity was observed [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ganciclovir (GCV) and its orally bioavailable prodrug, Valganciclovir, have served as gold standards for pre-emptive therapy and prophylaxis against HCMV in solid organ transplant patients [ 6 ] as well as for the treatment of CMV retinitis [ 7 ] for almost 30 years. However, their myelosuppressive potential precludes their prophylactic use in stem cell transplant recipients, which has led to their administration, mostly upon engraftment [ 8 ].…”
Section: Introductionmentioning
confidence: 99%